GNSS-SDR, un ricevitore software completamente open-source pronto per GALILEO - Branzanti, Mara (GEOmedia, 2014)
With the advent of new in-orbit satellites, the landscape of GNSS is going to change rapidly and thereceiver architectures must continuously be able to exploit the full potential of the forthcoming scenarios. For such reasons, the SDR (Software Defined Receiver) philosophy have a great response in the GNSS applications. Here, the first open source SDR software (GNSS-SDR) ready for the Galileo constellation is presented, together with its participation in the Google Summer of Code.